2017
DOI: 10.1039/c7ra02786a
|View full text |Cite
|
Sign up to set email alerts
|

Competitive biosorption behavior of Pt(iv) and Pd(ii) by Providencia vermicola

Abstract: Biosorption is an effective way to recover or remove metal ions from wastewater; however, the biosorption process in a multiple metal ion solution is still unclear. In this paper, we investigated the simultaneous biosorption in a Pt(IV) and Pd(II) binary system using Providencia vermicola. Kinetics, isotherms, thermodynamics, TEM, and FT-IR were carried out to elucidate the competition behavior and adsorption mechanisms in the process. The results revealed that Pd(II) had a relevant effect on the Pt(IV) biosor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The clear multi‐linearity for the three biosorbents implied the process involved more than one kinetic stage. The fastest sorption stage was attributed to the diffusional process of Pd (II) to the bacteria surface, and the second portion could be ascribed to intra‐particle diffusion with a delayed process The better fit of the pseudo‐second‐order model indicated that the chemical sorption, involving valency forces by exchange or sharing of electrons between sorbent and sorbate, was the rate‐limiting step which was similar to the results of the Elovich model.…”
Section: Resultssupporting
confidence: 56%
“…The clear multi‐linearity for the three biosorbents implied the process involved more than one kinetic stage. The fastest sorption stage was attributed to the diffusional process of Pd (II) to the bacteria surface, and the second portion could be ascribed to intra‐particle diffusion with a delayed process The better fit of the pseudo‐second‐order model indicated that the chemical sorption, involving valency forces by exchange or sharing of electrons between sorbent and sorbate, was the rate‐limiting step which was similar to the results of the Elovich model.…”
Section: Resultssupporting
confidence: 56%
“…Langmuir-type sorption occurs when the intermolecular forces decrease quickly with distance; that is, the surface of the biosorbent is covered by adsorbate, which forms a layer on the biomass. The linear Langmuir isotherm is given by [30]:…”
Section: = +mentioning
confidence: 99%
“…Providencia genus belongs to Enterobacteriaceae family of Enterobacteriales order of Gammaproteobacteria class, comprising of nine species of gram-negative rods 16 . Some strains of P. vermicola have been successfully incorporated in sequestration and biosorption of palladium, lead sulphite, and platinum 29 31 . Here, we report for the first time, the isolation of thoriotolerant P. thoriotolerans sp.…”
Section: Resultsmentioning
confidence: 99%